The answer would be 14 because I don’t know how to explain it
Answer:
cos = adjacent/hypotenuse
3/square root13
now you do square root 13 x3 divided by square root 13^2
= 3square root13/13
hope that answers your question
Answer:
x=-6
Step-by-step explanation:
-4x-2=22
Add two on both sides
-4x(-2+2)=22+2
-4x=24
Divide by negative 4
-4x/-4x=24/-4
Answer:
x=-6
I believe it is 2 because, 0.4 is added on to 2. 2.7 is basically 2.70 making it 0.70 bigger than 2.
I hope this helped
<span><span>(<span><span>(<span>−3</span>)</span><span>(2)</span></span>)</span><span>(3)</span></span><span>=<span><span>(<span>−6</span>)</span><span>(3)</span></span></span><span>=<span>−<span>18</span></span></span>